Visions of the university across a half-century - Neave, Guy R. (Paris : International Universities Bureau of the International Association of Universities, 2000)
The Year 2,000 marks an important moment in the life of the International Conference - the Eleventh in this series of meetings. It is also the Jubilee Year of our foundation in 1950 at Nice under the auspices of UNESCO. For fifty years, the Association has served as a forum where the leadership of the universities of the world may broach and debate issues of shared concern. For a half century, the Association has given substance and expression to that sense of global responsibility to which universities have naturally subscribed long before the term 'globalisation' itself came in vogue. Ten years ago, at the Helsinki General Conference, the Association presented an account of the first four decades of its saga. The commemorative essay, Universality, Diversity and Interdependence - IAU 1950 - 1990, was written with his customary sensitivity and brilliance by one of IAU's long-serving staff members, Georges Daillant, then Deputy Secretary General.
Part One. Reconstruction and order conferences, 1984-1970 -- I. University values -- II. Role and mission -- III. University and government -- IV. University and society -- Part Two. Growth and change conference, 1975-1997 -- IV. University values -- V. Role and mission -- VI. University and government -- VII. University and society.
Includes bibliographical references.
Keywords: HIGHER EDUCATION